Effect of Triiodothyronine in Different Dosages on Growth and Survival Rate of Giant Gouramy (Osphronemus gouramy Lac.) - I. Herviani; M. Zairin Junior; Odang Carman (Jurnal Akuakultur Indonesia)
This experiment was conducted to study the effect of giant gouramy larval immersion in triiodothyronine (T3) hormone solution on their growth and survival rate. One-day old larvae were treated with different concentrations of triiodothyronine (T3) i.e. 0; 0,001; 0,01; 0,1 and 1 ppm by immersion method for 24 hours. During eight weeks rearing period, larvae were fed to satiation with Tubifex three times daily. The media were aerated and changed 10-30% daily. At the end of experiment, there was no significant difference in yolk sac absorption between treated larvae and control. The highest dose of 1 ppm T3 resulted significant decreased in total length, average weight and survival rate of larvae.